Temperature, Relative Humidity and Photosynthetic Photon Flux Density Affects the Growth of Phyllanthus niruri L. Seedling - Adi Prabowo, Mohamad Khrisna; Irna Suryana Bidara; Siti Himawati; Eka Nurhangga; Rina Aprianti; Dwi Pangesti Handayani; Rizki Dwi Satrio; Winda Nawfetria (Politeknik Negeri Jember, 2024)
In order to obtain high-quality seedlings, the effects of temperature, relative humidity, and photosynthetic photon flux density (PPFD), the seed of Phyllanthus niruri L. (meniran) were investigated in different microclimate (temperature, relative humidity, PPFD) environments. The present study was conducted from February to May 2024 at the experimental greenhouse and screen house of the National Research and Innovation Agency, Banten, Indonesia. Microclimate parameters were observed thrice daily at 8 am, 12 pm, and 3 pm during the research. The two environments significantly differ in microclimate. The average temperatures, relative humidity, and PPFD of environment 1 are 35.30±5.04 oC, 60.95±17.40%, and 483.33±406.00 µmol m-2 S-1, while environment 2 are 33.07±4.84 oC, 70.47±16.63% and 356.4±339.55 µmol m-2 S-1. All treatments were repeated 18 times. After the 21-day treatment during the seedling stage, P. niruri seedlings were observed, including the germination rate, number of leaves, shoot length, and chlorophyll content index. Results showed that the germination rate, leaves, shoot length, and chlorophyll content index significantly differ between P. niruri seedlings in both environments. Phyllanthus niruri that grow in environment 1 have a higher germination rate than in environment 2, likewise, the number of leaves, shoot length, and chlorophyll content index. This initial research showed that P. niruri seedling grows better in an environment with temperature, relative humidity, and PPFD, respectively 35.30±5.04 oC, 60.95±17.40%, and 483.33±406.00 µmol m-2 S-1.